Do Tapping Box Technology Increase Local Taxes And District Own Source Revenue? - RATNAWATI, JULI; Anna Sumaryati; Enny Susilowati Mardjono; Melati Oktafiyani (Jurnal Akuntansi, 2023)
Taxes have a very important contribution to the state because they are the main income and a manifestation of community involvement in state spending which is regulated in laws. Local taxes as one of the many sources of District Own Source Revenue have a very important role in regional development. This local taxes collection and revenue must be maximized so that the resulting District Own Source Revenue will be maximized as well. The technological innovation or the use of Tapping Box has become an important part of taxes collection and revenue. The study aims to investigate restaurant taxes, the hotel taxes, and entertainment taxes on District Own OktafiyantiSource Revenue receipts mediated by the use of Tapping Box technology. The research took place in the Regional Finance Agency (BAPENDA) of Semarang Regency. This study uses a sample of 60 with 5 years of observation. The sample is the amount of taxes or income per month received from the Regional Taxes Information System then the acquisition of the collected data was analyzed using WarpPLS. The results show that the use of Tapping Box has proven to be able to strengthen the relationship between restaurant taxes and District Own Source Revenue and also the relationship between hotel taxes and District Own Source Revenue. On the other hand, the use of tapping boxes does not strengthen the relationship between the entertainment taxes and District Own Source Revenue. This indicates that the tapping box is often deactivated so that the entertainment business owner's income is not recorded every day, which causes the entertainment taxes paid to the local government to be not optimal.